Molecular Mechanisms of Carbapenem Resistance Among Enterobacteriaceae Isolated at Teaching Hospital, Batticaloa - Mohammed Shaheed Shihana; V Francis; V Liyanapathirana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The family Enterobacteriaceae includes a group of Gram negative facultative anaerobes. Members of this family are known to develop resistance to β- lactam antibiotics including carbapenems. Present study was carried out to identify presence of selected genetic determinants of carbapenem resistance in carbapenem non-susceptible Enterobacteriaceae at Teaching Hospital, Batticaloa. Isolates which were resistant or intermediate sensitive to any of carbapenems using routine sensitivity testing (CLSI) were collected from October 2015 to March 2016, sub cultured on blood agar and MacConkey agar and incubated in air at 37 0C for 18 – 24 hours. PCR amplification of blaTEM, blaSHV and blaCTX – M as potential genetic determinants of Extended Spectrum Beta Lactamases (ESBLs) and blaOXA – 48, blaKPC and blaNDM as genetic determinants for carbapenemases was performed. Total of 768 Enterobacteriaceae were isolated during study period and of these 5 were confirmed as resistant to carbapenem group i.e. carbapenem-resistant Enterobacteriaceae (CRE). All five isolates were intermediate resistant or resistant to imipenem, meropenem, ertapenem, ceftazidime, cefotaxime, ciprofloxacin, levofloxacin and aztreonam. Four isolates carried at least one potential genetic determinant of blaCTX – M in 3, blaTEM in 3 and blaSHV in 2 isolates. Four isolates were found to carry at least one of genetic determinants of blaOXA – 48 in 3 and blaNDM in 1.